Desentralisasi Fiskal, Efektivitas Penyerapan Anggaran, Belanja Modal, Level Maturitas Sistem Pengendalian Internal dan Akuntabilitas Pelaporan Keuangan Pemerintah Daerah: Kinerja Pemerintah Daerah sebagai Variabel Moderasi - Rahmat Rizal Muafiq; Anis Chariri (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of fiscal decentralization, the effectiveness of budget absorption, capital expenditure, the maturity level of the government's internal control system on the accountability of local government financial reporting with performance as a moderating variable. This research was conducted using quantitative methods using secondary data obtained from each agency related to the variable. The data used in this study uses secondary data taken from Local Government Financial Reporting in Central Java Province in the 2016 -2018 The results of the study show that the variables of fiscal decentralization, the effectiveness of budget absorption, and capital expenditure have no effect on the accountability of local government financial reporting. Meanwhile, the maturity level variable of the government's internal control system influences the accountability of local government financial reporting. Local government performance does not moderate the relationship between fiscal decentralization, effectiveness of budget absorption, and capital spending on the accountability of local government financial reporting. Local government performance can moderate the relationship between the maturity level of the government's internal control system on the accountability of local government financial reporting